Combined Proteomics and Transcriptomics Identifies Carboxypeptidase B1 and Nuclear Factor κB (NF-κB) Associated Proteins as Putative Biomarkers of Metastasis in Low Grade Breast Cancer - Bouchal, Pavel; Dvořáková, Monika; Roumeliotis, Theodoros; Bortlíček, Zbyněk; Ihnatová, Ivana; Procházková, Iva; Ho, Jenny T C; Maryáš, Josef; Imrichová, Hana; Budinská, Eva; Vyzula, Rostislav; Garbis, Spiros D; et al. (Molecular & cellular proteomics, 2015)
Current prognostic factors are insufficient for precise risk-discrimination in breast cancer patients with low grade breast tumors, which, in disagreement with theoretical prognosis, occasionally form early lymph node metastasis. To identify markers for this group of patients, we employed iTRAQ-2DLC-MS/MS proteomics to 24 lymph node positive and 24 lymph node negative grade 1 luminal A primary breast tumors. Another group of 48 high-grade tumors (luminal B, triple negative, Her-2 subtypes) was also analyzed to investigate marker specificity for grade 1 luminal A tumors. From the total of 4405 proteins identified (FDR < 5%), the top 65 differentially expressed together with 30 previously identified and control markers were analyzed also at transcript level. Increased levels of carboxypeptidase B1 (CPB1), PDZ and LIM domain protein 2 (PDLIM2), and ring finger protein 25 (RNF25) were associated specifically with lymph node positive grade 1 tumors, whereas stathmin 1 (STMN1) and thymosin beta 10 (TMSB10) associated with aggressive tumor phenotype also in high grade tumors at both protein and transcript level. For CPB1, these differences were also observed by immunohistochemical analysis on tissue microarrays. Up-regulation of putative biomarkers in lymph node positive (versus negative) luminal A tumors was validated by gene expression analysis of an independent published data set (n = 343) for CPB1 (p = 0.00155), PDLIM2 (p = 0.02027) and RELA (p = 0.00015). Moreover, statistically significant connections with patient survival were identified in another public data set (n = 1678). Our findings indicate unique pro-metastatic mechanisms in grade 1 tumors that can include up-regulation of CPB1, activation of NF-κB pathway and changes in cell survival and cytoskeleton. These putative biomarkers have potential to identify the specific minor subpopulation of breast cancer patients with low grade tumors who are at higher than expected risk of recurrence and who would benefit from more intensive follow-up and may require more personalized therapy.
Keywords: Gene Expression Regulation, Neoplastic; Isotope Labeling; Neoplasm Metastasis; Carboxypeptidase B; karboxypeptidasa B; Neoplasm Grading; Kaplan-Meier Estimate; regulace genové exprese u nádorů; Kaplanův-Meierův odhad; imunohistochemie; nádory prsu; Databases, Protein; stanovení celkové genové exprese; reprodukovatelnost výsledků; Reproducibility of Results; Gene Expression Profiling; proteomika; lidé; izotopové značení; ženské pohlaví; Immunohistochemistry; Breast Neoplasms; stupeň nádoru; Humans; NF-kappa B; Proteomics; databáze proteinů; Female; metastázy nádorů; Biomarkers, Tumor; nádorové biomarkery